Rosa Maria Motta. Material culture and cultural identity: a study of Greek and Roman coins from Dora - Rutter, Keith (Journal of Greek Archaeology, 2016)
This book studies the coinage of Dora, an ancient port city on the coast of Israel about 14 miles south of Haifa. As its title (Material Culture and Cultural Identity) suggests, the book concentrates on ‘all possible interpretations that contribute to the Dora narrative’ (p. 30). In fact, the book is heavy on theory, but it is a serious drawback that it does not provide the fundamental numismatic basis of a thoroughly revised, accurate and well-illustrated catalogue of the coins. The numismatic material in the book relies on an article by Meshorer, but we need a new catalogue both for its own sake and to justify elements in the discussion, for example, remarks about the commonness of various issues which occur from time to time, or the overall output of the mint.